The performance of UiTM Sarawak MDAB pre-science graduates at diploma level : A tracer study / Nor Hazizah Julaihi ... [et al.] - Julaihi, Nor Hazizah; Mohamed, Bebe Norlita; Karim, Mariathy (2016)
The MDAB Pre-Science program is a remedial course introduced by Universiti Teknologi MARA (UiTM) in June 2011. The main objective of the program is to give an opportunity to Bumiputera students having under qualified entry results and coming from low income family to further their tertiary studies in UiTM. Through this program, some students who did not perform well in their SPM managed to ernbark to university and excel in their Pre-Science program and later in their Diploma studies. The research was embarked to trace the performance of the Pre-Science graduates in their respective Diploma studies at UiTM Sarawak. Specifically, this research aims to share some analysis gathered on the overall performance of MDAB students for the past 9 semesters of intakes for the whole UiTM system, to study the performance of Pre-Science students in the first 6 semesters of MDAB intakes particularly at UiTM Sarawak, to Investigate the performance of MDAB Pre-Science graduates in their Diploma studies at UiTM Sarawak, and finally, to obtain meaningful information regarding the MDAB Pre-Science initiatives through students' responses obtained from the online survey and interviews.